Factors associated to the access of prenatal care in the hospitals of Huaral and Chancay, Peru - Rivera Felix, Lauro Marcoantonio (2018)
Introduction. Prenatal care still does not cover the total of pregnant women, a situation that is repeated in Latin America and the few that evaluate the barriers that explain this phenomenon. The objective of study was to determine the factors associated with the access of prenatal care in its opportunity and coverage dimensions. Methods. Study of quantitative, observational, analytical approach carried out in 110 schools of the Hospitals of Huaral and Chancay, Peru. The factors (personal and sociodemographic) associated with access to prenatal care were evaluated according to their coverage (minimum 6 controls) and timely care (first control <14 weeks). A multivariate logistic regression analysis was performed considering a confidence level of 95%. Results. It was found that forgetfulness of appointments is shown as a factor associated with inadequate coverage of antenatal care (p=0,048), while the presence of a safe state of prenatal care was associated with timely prenatal care (p=0,013). Conclusions. The absence of forgetfulness of appointments and the presence of a safe state of health during pregnancy is associated with access to prenatal care.